The Influence Of Financial Literacy, Financial Planning And The Use Of Fintech Applications On The Financial Independence Of Management Students At Panca Budi Development University - Nur Hafizah Fatimah; Syahrial Hasanuddin; Ramadhan Harahap (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of financial literacy, financial planning, and the use of fintech applications on the financial independence of management students at Universitas Pembangunan Panca Budi, Medan. The research employs a quantitative approach. Data were collected using purposive sampling by distributing questionnaires through Google Forms, which were shared via WhatsApp chats and Instagram direct messages to obtain respondents. The measurement scale used was a Likert scale ranging from 1 to 5.The population and sample of this study consist of management students at Universitas Pembangunan Panca Budi, Medan. Data analysis was conducted using SPSS to examine the simultaneous effects of financial literacy, financial planning, and fintech application usage on students’ financial independence. The analysis included data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R²). The results indicate that the independent variables have a significant effect on the dependent variable, supporting the hypotheses proposed in this study.